Policy in Clinical Practice: Choosing Post‐Acute Care in the New Decade. Issue 3 (17th February 2021) - Makam, Anil N; Grabowski, David C
Abstract : Nearly half of hospitalized Medicare patients in 2018 were discharged to post‐acute care (PAC), accounting for approximately $60 billion in annual spending. There are four PAC settings, and these vary in the intensity and complexity of medical, skilled nursing, and rehabilitative services provided; each setting uses a separate payment system. Due to considerable variation in PAC use, with concerns that similar patients can be treated in different PAC settings, the Centers for Medicare & Medicaid Services (CMS) recently introduced several major policy changes. For home health agencies (HHAs) and skilled nursing facilities (SNFs), CMS implemented new payment models to better align payment with patients' care needs rather than the provision of rehabilitation. For long‐term acute care hospitals, CMS will now decrease payment for less medically ill patients. To choose PAC wisely, hospitalists and hospital leaders must understand how these new policies will change where patients can be discharged and the services these patients receive at these PAC settings.